Characterising the enzyme-driven metabolic shifts in rancid pearl millet flour using metabolomics approaches: a step towards improving quality and shelf-life - Kumar, Ranjeet R.; Kumar, Ashok; Vinutha, T.; Goswami, Suneha; Kumar, Sudhir; Singh, Sumerpal; Manjunath Prasad, C. T.; Mishra, Gyan P.; Padaria, Jasdeep C.; Jha, Girish K.; Chellapilla, Tara Satyavathi; Chinnusamy, Viswanathan (Frontiers in Nutrition, 2025)
Rancidity significantly limits the shelf-life and market potential of pearl millet flour and its processed food items, despite the grain’s nutritional superiority. This study employed a comprehensive metabolomic and biochemical approach to unravel the mechanisms underlying rancidity in pearl millet cultivars—Pusa-1201 (hybrid) and Chadhi Bajri (landrace). Untargeted LC–MS profiling revealed pronounced metabolic alterations in stored flour of Pusa-1201, with elevated levels of lipid degradation products (3-oxotetradecanoyl-CoA), pigments (chlorophyllide b), free fatty acids, etc. In contrast, Chadhi Bajri exhibited unique antioxidant and stress-protective metabolites (quercetin 3-sulfate, rosmarinate), indicating greater resistance to oxidative degradation. Enzymatic assays showed a storage-dependent increase in lipase, lipoxygenase, peroxidase, and polyphenol oxidase activities—particularly in Pusa-1201—correlating strongly with rancidity indices, including acid value (AV), peroxide value (PV), and free fatty acid content (FFA). Multivariate statistical analyses (PLS-DA, VIP plots, heat-maps) highlighted discriminatory metabolites contributing to rancidity progression and oxidative stress. A set of 25 metabolites, including phytol, ethanolamine, chlorophyllide b, and glucoside derivatives, emerged as key biomarkers of rancidity. These findings provide valuable insights for developing metabolite-based sensors to assess rancidity behaviour across diverse pearl millet accessions. Further, the information can be used to develop technology for enhancing flour’s stability and utilisation in developing processed food products.